Advanced Variance Analysis Of Functions Containing Quotients: Avoiding Information Loss From Treating Ratios As A Single Variable (The Journal of Theoretical Accounting Research, 2025)
Variance analysis calculations are commonly performed on a two-variable product.  In cases of the original function being a three-variable quotient, often the first step is to divide one variable in the numerator by another variable in the denominator, resulting in one new, aggregate variable replacing the original two.  Such reduction to a two-variable function leads to a loss of information.  This article presents models designed to avoid the aggregation of variables, to be used with only original variables.  The models incorporate the concept of responsibility centers, allowing for a more appropriate set of variance analysis calculations for the firm.